Stakeholder Perspectives on Energy Auctions: A Case Study in Roraima, Brazil - Villas-Bôas, Pedro Meirelles [UNESP]; Jardim da Silveira, José Maria Ferreira; Villas-Bôas, Fernando Rocha (MDPI, 2023)
Energy auctions are commonly used to contract energy projects and are extensively studied from the regulator’s perspective. However, analyzing auctions from the stakeholders’ perspective is critical to determine the impact of regulatory details on the bidder’s revenues. In this study, we analyze a public energy auction in Roraima, a Brazilian state with a significant energy deficit and no grid connection, where many projects were successful in the non-intermittent Power Product category, typically unfavorable for biomass. Using Linear Programming to maximize bidders’ revenues, we examine the regulatory formulas that contributed to the success of these projects and compare the optimization results to actual revenues. Our analysis shows that certain regulatory elements can benefit stakeholders by allowing them to make unconventional project design decisions. In addition, we identify a possible loophole in the formula that can have the opposite effect of the regulator’s intent in the renewable Power Product category. Our findings can help bidders increase profits through optimization and regulators to change formulas if objectives are not met. This study brings the often-overlooked perspective of stakeholders to energy auctions, adding to the literature on this topic.
Keywords: energy auctions; non-intermittent power product; profit optimization; project design; stakeholder perspective